Immediate Psychological Responses, Stress Factors, and Coping Behaviors in Military Health-Care Professionals During the COVID-19 Pandemic in Tunisia - Slama, Hela; El Kefi, Hamdi; Taamallah, Karima; Stambouli, Nejla; Baffoun, Anis; Samoud, Walid; Bechikh, Chaker; Oumaya, Abdelaziz; Lamine, Khaled; Hmida, Mohamed Jalel; Slama, Hichem; Ferjani, Mustapha; et al. (Frontiers in Psychiatry, 2021)
Objective: The COVID-19 epidemic began in Tunisia in March 2020; health-care workers (HCWs) were suddenly confronted with a particularly stressful situation. The aim of this study was to assess the psychological responses of HCWs during the epidemic, determine the stressors and identify ways to cope. Methods: This cross-sectional study used an online questionnaire that included 62 questions. ANOVAs and t-tests were used to compare the responses between professional groups, age groups, and genders. Results: Questionnaires were completed by 368 HCWs. HCWs believed they had a social and professional obligation to continue working long hours (95.3%). They were anxious regarding their safety (93.7%) and the safety of their families (97.8%). Youthful age (p = 0.044) and female gender (ps <0.046) were identified as stressors. The availability of personal protective equipment (PPE; 99.7%) and good communication between colleagues (98.1%) and managers (91.6%) were important protective factors. Family and friend support (95.9%), following strict protective measures (99.4%), knowing more about COVID-19 (94.8%), adopting a positive attitude (89.6%), and engaging in leisure activities (96.1%) helped in dealing with this epidemic. Conclusion: This study highlights the importance of providing HCWs with infection control guidelines and adequate PPE. Communication and support within the team and maintaining family support help in coping with this stressful situation.